Arkansas politics and government - Blair, Diane D., 1938- (Politics and governments of the American states., 2005)
"Published a decade and a half after the late Diane D. Blair's influential book Arkansas Politics and Government, this freshly revised edition builds on her work, which highlighted both the decades of failure by Arkansas's government to live up to the state's motto of Regnat Populus ("The People Rule") and the positive trends of democracy." "While maintaining the basic structure of Blair's original work with its focus on important historical patterns and the ways in which the past continues to shape the present, the second edition details the causes and consequences of recent changes in Arkansas and asks whether they are profound and permanent or merely transitory variations in symbol and style. Jay Barth argues that although Arkansas currently expresses a healthier representative democracy than throughout most of its history, its political and governmental entities are still sharply limited as effective instruments of "the people.""--Jacket